2007
DOI: 10.1186/1746-4269-3-9
|View full text |Cite
|
Sign up to set email alerts
|

Whales, dolphins or fishes? The ethnotaxonomy of cetaceans in São Sebastião, Brazil

Abstract: The local knowledge of human populations about the natural world has been addressed through ethnobiological studies, especially concerning resources uses and their management. Several criteria, such as morphology, ecology, behavior, utility and salience, have been used by local communities to classify plants and animals. Studies regarding fishers' knowledge on cetaceans in the world, especially in Brazil, began in the last decade. Our objective is to investigate the folk classification by fishers concerning ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 27 publications
2
29
0
1
Order By: Relevance
“…High correspondence emphasizes the importance of considering the local fishermen’s knowledge and accumulated experience in biological inventories [62], besides contributing to the development of management plans for fishery resources [43,63,64]. …”
Section: Resultsmentioning
confidence: 99%
“…High correspondence emphasizes the importance of considering the local fishermen’s knowledge and accumulated experience in biological inventories [62], besides contributing to the development of management plans for fishery resources [43,63,64]. …”
Section: Resultsmentioning
confidence: 99%
“…The northern portion of this coast encompasses the municipalities of Ubatuba, Caraguatatuba, São Sebastião and Ilhabela (Souza and Begossi 2007). São Sebastião (23°42′18″ to 23°45′38″ S-45°25′41″ to 45°53′49″W) is composed of a narrow lowland area between the sea and the slopes of the Atlantic Forest and is inhabited by almost 70,000 persons (IBGE 2000).…”
Section: Study Areamentioning
confidence: 99%
“…However, in Brazil, ethnobiological studies are reported for the states of Rio de Janeiro (RJ) (Zappes et al, 2010;2011a), São Paulo (SP) (Souza, 2007;Souza and Begossi, 2007), Santa Catarina (SC) (Simões-Lopes, 1991;Simões-Lopes and Daura-Jorge, 2008) and Rio Grande do Sul (RS) (Simões-Lopes, 1991;Zappes et al, 2011b;2013;. In Cagarras Archipelago (RJ), southeastern Brazil, a study aimed to identify the possible interactions and conflicts between the bottlenose dolphins and fisheries through the traditional knowledge (Zappes et al, 2011a).…”
Section: Results Of Previous Studiesmentioning
confidence: 99%
“…In São Sebastião (SP) a study about the popular taxonomy of cetaceans indicated that the bottlenose dolphin is classified by fishermen as part of the genus boto and/or golfinho, belonging to the ethnospecies boto-caldeirão and/or golfinhoflíper (Souza, 2007;Souza and Begossi, 2007).…”
Section: Results Of Previous Studiesmentioning
confidence: 99%